The Role and Significance of Tax Incentives in the Business Activity of Entrepreneurs and Increasing the Country Budget: Mediating Role of Supply Chain Management - D.I Razakova; S.K Nurymova; M.M Khalitova; S.S Tamenova; U.M Iskakov; M Konyrbekov (International Journal of Supply Chain Management, 2020)
Abstract- This primary objective of this investigation is to investigate the relationship between tax system, entrepreneurship, tax incentives and country economy growth with the mediation effect of supply chain management.  The analysis of the order and procedure for tax revenues for the treasury, the role of tax revenues in increasing the revenue of the state budget, the value of tax incentives in the business activity of business entities and increasing the country's budget, as well as the effectiveness of tax administration in the Republic of Kazakhstan has been performed in this article.